3D Particle Position Measurement via the Defocusing Concept - Bao, Xiaoli; Li, Muguo (International Journal of Advanced Science and Technology, 2010)
This paper presents a 3D particle position measurement method based on the defocusing concept introduced by A.Pentland with a single camera. Different from the existing approaches, the blur circle is used to identify the blur extent for various defocused particles, and the depth-blur relation is formulated by the modified A.Pentland mathematical formula. And, an eight-step algorithm based on Circular Hough Transform and Quadrant Radius Histogram was given to calculate the 3D particle position. Experiments on real defocused particle images have demonstrated the feasibility of the proposed method for 3D particle position recovery, and the minimum Mean Absolute Error of depth is about 0.18 mm.